2004
DOI: 10.1002/chir.20034
|View full text |Cite
|
Sign up to set email alerts
|

Programmed assembly of rigid-rod ?-barrel pores: Thermal inversion of chirality

Abstract: The programmed assembly of p-octiphenyl rods carrying six complementary tripeptide strands was studied in the presence of bilayer membranes using circular dichroism (CD) spectroscopy. Thermal CD experiments demonstrated programmed assembly of anionic and cationic rods into supramolecules at low temperature that irreversibly transform into more stable supramolecules at intermediate and high temperature. Higher activation energies for programmed assembly with rods containing multiple guanidinium rather than ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It is most interesting perhaps that this polycationic pore can be used for cation-selective transport, as well as being a small anion channel (∼3.3 Å) that can host large anionic guests (HPTS). Also, in comparison to other internal functional arrangements, these pores show an extended single-channel lifetime of up to 20 s. In a somewhat related study, using thermal CD experiments and p -octiphenyl rods carrying complementary tripeptide strands functionalized with arginine residues, it was shown that annealing of the rods with temperature lead to an inversion of supramolecular chirality . This took place because the high temperature allowed exchange of phosphate from the guanidinium residue by glutamate residues in a programmed assembly environment.…”
Section: 2 Synthetic Guanidinium Groups/selectors/ligands/receptorsmentioning
confidence: 96%
“…It is most interesting perhaps that this polycationic pore can be used for cation-selective transport, as well as being a small anion channel (∼3.3 Å) that can host large anionic guests (HPTS). Also, in comparison to other internal functional arrangements, these pores show an extended single-channel lifetime of up to 20 s. In a somewhat related study, using thermal CD experiments and p -octiphenyl rods carrying complementary tripeptide strands functionalized with arginine residues, it was shown that annealing of the rods with temperature lead to an inversion of supramolecular chirality . This took place because the high temperature allowed exchange of phosphate from the guanidinium residue by glutamate residues in a programmed assembly environment.…”
Section: 2 Synthetic Guanidinium Groups/selectors/ligands/receptorsmentioning
confidence: 96%
“…65 These data indicate that nanotubes formed from these peptides insert into the cell wall of the bacterium, which results in rapid cell death. Another example of peptides that are assembled into intermolecular structures leading to ion channels is described by Sakai et al 66 The authors described the programmed assembly of anionic p-octiphenyls with homologous molecules containing guanidinium and ammonium cations into supramolecular oligomers and polymers in the presence of spherical lipid bilayers (Fig. 10).…”
Section: Self-assembled Nanotubesmentioning
confidence: 99%
“…Although the chiral p-octiphenyl chromophores can serve as marvelous intrinsic circular dichroism (CD) probes, even the sensitivity of CD spectroscopy is only marginally sufficient for measurements under conditions relevant for function. [7][8][9]11,12,[46][47][48][49][50] This leaves fluorescence spectroscopy as the method of choice for necessarily low-resolution structural studies. Direct evidence from fluorescence depth quenching (FDQ) for transmembrane pore orientation as drawn in Figures 3-5 is, for instance, one of the rare examples for important and otherwise "hard-to-get" structural information that is accessible without extraordinary efforts under conditions relevant for function (compare Sec.…”
Section: Feature Articlementioning
confidence: 99%